Enhanced void swelling in NiCoFeCrPd high-entropy alloy by indentation-induced dislocations. Issue 10 (3rd October 2018) - Lu, Chenyang; Yang, Taini; Jin, Ke; Velisa, Gihan; Xiu, Pengyuan; Song, Miao; Peng, Qing; Gao, Fei; Zhang, Yanwen; Bei, Hongbin; Weber, William J.; Wang, Lumin
ABSTRACT: The role of dislocations on ion irradiation-induced void formation is studied in a high-entropy alloy (HEA) NiCoFeCrPd. Despite previous observations that show high-entropy alloys are swelling resistant due to a high defect recombination rate, the swelling is enhanced with increasing density of pre-existing dislocations at low strain levels that shortened transient duration before the onset of void swelling. Under certain irradiation conditions, a high density of dislocations may carry the material closer to the sink-dominated regime. Compared to another HEA NiCoFeCrMn, NiCoFeCrPd has a smaller loop size and higher loop density due to the stronger lattice distortion. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Swelling behavior in a newly designed high-entropy alloy NiCoFeCrPd has been studied for the first time. Void swelling is enhanced with increasing density of pre-existing dislocations in NiCoFeCrPd.